Validation and Evaluation of Two Observational Pain Assessment Tools in a Trauma and Neurosurgical Intensive Care Unit - Jane Topolovec-Vranic; Celine Gélinas; Yangmei Li; Mary Ann Pollmann-Mudryj; Jennifer Innis; Amanda McFarlan; Sonya Canzian (Pain Research and Management)
BACKGROUND: Studies have demonstrated that patients in the intensive care unit experience high levels of pain. While many of these patients are nonverbal at some point during their stay, there are few valid tools available to assess pain in this group.